2017
DOI: 10.1038/s41598-017-11807-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic analysis of the toluene degrading black yeast Cladophialophora immunda

Abstract: Cladophialophora immunda is an ascomycotal species belonging to the group of the black yeasts. These fungi have a thick and melanized cell wall and other physiological adaptations that allows them to cope with several extreme physical and chemical conditions. Member of the group can colonize some of the most extremophilic environments on Earth. Cladophialophora immunda together with a few other species of the order Chaetothyriales show a special association with hydrocarbon polluted environments. The finding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 89 publications
0
34
0
Order By: Relevance
“…Studies have demonstrated that toluene triggers the expression of fungal antioxidants to induce cell detoxification and to reduce the impact of the damage caused by ROS (Blasi et al ., 2017). In this study, fungi growing at 0.01 and 0.10% toluene showed marked resistance to H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that toluene triggers the expression of fungal antioxidants to induce cell detoxification and to reduce the impact of the damage caused by ROS (Blasi et al ., 2017). In this study, fungi growing at 0.01 and 0.10% toluene showed marked resistance to H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the abundance and high diversity of CYPs in Chaetothyriales (Teixeira et al 2017;Vicente et al 2017), this family of enzymes has been suggested to play an essential role in the adaptation to extreme environments. For example, in the hydrocarbon degrading fungus Cladophialora immunda, CYPs are among the most overrepresented protein domains and are upregulated when the fungus was grown in the presence of toluene (Blasi et al 2017). Indeed, recent studies have concluded that some families of CYPs are associated with the initial oxidation of the methyl group of toluene being one of the key reactions for the degradation of pollutants (Luykx et al 2003;Blasi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the hydrocarbon degrading fungus Cladophialora immunda, CYPs are among the most overrepresented protein domains and are upregulated when the fungus was grown in the presence of toluene (Blasi et al 2017). Indeed, recent studies have concluded that some families of CYPs are associated with the initial oxidation of the methyl group of toluene being one of the key reactions for the degradation of pollutants (Luykx et al 2003;Blasi et al 2017). CYPs are essential for the metabolism of polycyclic aromatic hydrocarbons from multiple anthropogenic sources, such as oil spills and incomplete combustion of organic materials (e.g., coal, oil, petrol, and wood) (Abdel-Shafy and Mansour 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations